Using small punch test data to determine creep strain and strength reduction properties for heat affected zones. (January 2014) - Holmström, S.; Auerkari, P.; Hurst, R.; Blagoeva, D.
<x content-type="archive" xml:space="preserve">Abstract</x> The small punch (SP) test is a miniature technique that can provide information on creep performance of local features in welded components. However, the multiaxial stress and deformation history in SP test means that it can be a challenge to interpret the test results in a way that is comparable to uniaxial standard creep testing. This work aimed to compare SP test results from as new and service exposed P91 (9Cr–1Mo–V–Nb) base material (BM) and heat affected zones (HAZ) to uniaxial creep testing results from welded new and service exposed material. Two methods are proposed for predicting the uniaxial strain response for any zone of the weld: one alternative is to apply the SP rupture data and to accommodate the shape of the uniaxial base material creep curve to that of the zone of interest in the SP test. The other alternative is to use the SP deflection data and an appropriate translation function to the uniaxial creep curve. In both cases, the Wilshire creep equations have been used as the rupture model. The approach will also predict the stress reduction factors of welds and its constituent parts (including the subzones of HAZ). It is proposed that the approach is used to provide the local constitutive creep models for component assessment by finite element analysis (FEA).